Spatial distribution characteristics, ecological risk assessment, and source analysis of heavy metal(loid)s in surface sediments of the nearshore area of Qionghai - Jiang, Junyi; Fu, Miao; Yang, Jianying; Song, Yanwei; Fu, Guowei; Wang, Hongbing; Lin, Cong; Wang, Yang (Frontiers in Marine Science, 2024)
To understand the pollution characteristics and potential sources of heavy metal(loid)s in the nearshore sediments of Qionghai, 93 surface sediment samples were collected from the region. The concentrations of 20 elements, including Fe, Mg, Ca, Ti, Mn, Ba, Cr, Sr, Ni, Cu, Zr, As, Hg, Se, Be, Co, Mo, Cd, Ga, and Pb, were measured. The extent of contamination and ecological risk posed by these heavy metals/metalloids were evaluated using the geo-accumulation index, potential ecological risk index, and Nemerow comprehensive risk index. Additionally, correlation analysis, principal component analysis (PCA), and positive matrix factorization (PMF) were employed to identify the potential sources of these elements in the sediments. The findings reveal the following: (1) The mean concentrations of Fe, Ca, Mg, Ti, Cu, Sr, Zr, Mo, Cd, Pb, Hg, As, and Se exceed the background values for shallow sea sediments in China. Notably, Ca, Ti, Sr, Zr, Mo, Hg, and As exhibit coefficients of variation greater than 51%, indicating significant spatial variability primarily driven by anthropogenic activities. (2) The ecological risk assessment identifies Sr, Hg, and As as the principal pollutants and key potential ecological risk factors in the study area, necessitating prioritization in subsequent monitoring efforts. (3) Correlation and source analysis suggest that As and Mn primarily originate from agricultural activities, Sr, Ca, and Mg from aquaculture, Zr, Ti, Mo, Se, Pb, Be, Co, Cu, Ga, Ni, Fe, and Cd from natural sources, and Hg, Ba, and Cr from transportation sources. Additionally, this study identified Sr, Hg, and As as the primary pollutants in the Qionghai nearshore area, with sources predominantly linked to agriculture, aquaculture, and traffic. Regular monitoring will help track the effectiveness of implemented control measures and provide data for ongoing risk assessments, ensuring the protection and sustainability of the marine environment.